Forward-Looking Information Disclosure: Leverage, Profitabilitas, Jumlah Komite Audit, Komisaris Independen, Frekuensi Rapat Komite Audit - Adella Anindya Putri Mahardika; Eny Kusumawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Forward-looking information disclosure (FLID) is a category of information regarding future forecasts that allow users to assess the company's future performance. This study analyzes the effect of leverage, profitability, number of audit committees, independent commissioners, and frequency of audit committee meetings on nonfinancial companies listed on the Indonesia Stock Exchange for the period 2021-2023. The sampling technique used in this study was purposive sampling. A total of 627 companies have met the criteria as observation units. The analysis method used is multiple linear regression analysis and has passed the classical assumption test. The results provide empirical evidence that profitability and the number of audit committees have a proven effect on FLID. Meanwhile, leverage, independent commissioners, and the frequency of audit committee meetings have no effect on forward-looking information disclosure. These findings provide insight for companies, investors, and regulators in disclosing their financial statements. This study provides recommendations for future research to expand sample coverage and consider other factors that may affect FLID, such as managerial ownership, public ownership, or company size.